Pedagogy-walk the walk, don't talk the talk. An opinion piece. Issue 1 (1st January 2020) - Young, Tim
ABSTRACT: In this opinion piece I reflect on an inspiring 2019 Advance HE STEM conference in Birmingham. In doing so I identify the term pedagogy as one aspect which ran contrary to the noble aspirations of the conference. I outline my own perspective as both an insider and outsider in my role of a Teacher-Practitioner. I use this vantage point to outline the background to the term pedagogy together with its suggested alternatives. I review the roots of the word itself to suggest that instead of overusing the term pedagogy, we should focus more on the journey of education we are privileged to share with our students.